Pendampingan Diversifikasi Olahan Tahu sebagai Usaha Sampingan Ibu Rumah Tangga di Desa Banjaransari Ngawi (Lembaga Pengembangan Kinerja Dosen, 2026)
The Community Empowerment Practice (PPM) Group 1 of the Indonesian Institute of Indonesian Students Association (IAI) Ngawi in Banjaransari Village, Padas District, Ngawi Regency aims to increase the economic productivity of housewives through the utilization of local commodities, including tofu. The community service partners faced challenges such as a lack of variety in tofu processing methods and limited knowledge regarding home-based side business management. The method used was participatory action research (PAR), which included outreach, training on innovative tofu products (Tahu Fantasi, Dimsum Tahu, and Tahu Walik), and product packaging education. The results of this activity showed an 85% increase in the partners' skills in processing tofu into higher-value products, as well as increased motivation to start side businesses to support family economic stability. Thus, empowerment activities centered on innovative processed tofu products are expected to serve as an alternative means to increase income, strengthen economic self-reliance, and support sustainable family economic stability.